Bullying victimization among school- going adolescents in Iraq - Yahya, Hyder M.; Hashim, Mushtaq T.; Al-Kaseer, Eman A.; Al-Diwan, Jawad K. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Bullying victimization is a major public health problem. Interest in bullying in Arab world is a recent phenomenon. Publication on victimization in Iraq is scares. Therefore this study was conducted to report bullying among students of Iraqi schools.Methods: A total of 302 students from Baghdad was selected by a cluster random sample to include in this study. An Arabic version of standardized questionnaire was obtained from the International (ISPCAN). Identification of bullying (bullies, victims and sexual victims) was done by using a cutoff for the scoring of bullying manifestation in the questionnaire depending on three repeated action at least to consider as bullies. P value less than 0.05 was considered significant for meeting the criteria of bullying.Results: Out of the total 39.1% were bullied pupils (victims) there was a significant association between bullying and victim with sex (P=0.001). Bullying and victimization was significantly associated with smoking, drug abuse, and failure in school (P=0.001 for each).Conclusion: High prevalence of victimization (bully, victims and sexual victim was revealed among students in schools as a predictor for smoking and drug abuse.